Aesthetic Installations of J. Dryden and the Cromwellian Myth in “Heroic Stanzas for the Death of Oliver Cromwell” (Proceedings of Southern Federal University. Philology, 2019)
Andrey M. Berdichevsky (Rostov-on-Don, Russian Federation)In this article the author essays to remonstrate the widely spread characteristic of the poem as wholly eulogic and non-conceptional In the first part he argues Dryden to understand Cromwell`s glorification here as an intellectual task: it`s Dryden`s response at the challenge to the pictorial power of poetry by Cromwell`s “perfect fame”. In the second part the author reconstructs and examines the Cromwellian mythos, created by Dryden in “ Stanzas”, that interprets the initial contradiction. In the conclusion the author compares the Renaissance and classicistic concepts of the poetry`s purposes and instruments. He concludes, that Cromwell phenomenon as the poetical object, constructed by Dryden, contradicts the foundations of classicistic aesthetics.Key words: Dryden, aesthetic issues, Cromwell, Cromwellian mythos, “ Heroic stanzas”, sphere of essence, sphere of appearance, virtue, universal order, ratonalism, classicistic aesthetics.DOI 10.23683/1995-0640-2019-1-167-176